Urgency and Emergency of Our Own Epistemology: A Cosmogony of the Psyche - León, Luis Eduardo (Rastros Rostros, 2012)
"The Meeting and Development of the Self from the Living of the Ancestral Indigenous Kogi Cosmogony of the Sierra Nevada de Santa Marta in Colombia’’ is the research that gives rise to this paper; it is developed in 2011-2012, conducted by the research group "Bouloumai" and belongs to the line of research in ancestral psychology of the program of Psychology at Universidad Cooperativa de Colombia in Bogota. Presented here is a forewarned and conscious intention on the need to look into the knowledge. philosophies and psychologies more typical of a South American reality as integrating evidence of perennial and scientific wisdom versus man’s quest at its core.